2020
DOI: 10.1364/optica.389982
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral multiphoton microscopy for in vivo visualization of multiple, spectrally overlapped fluorescent labels

Abstract: The insensitivity of multiphoton microscopy to optical scattering enables high-resolution, high-contrast imaging deep into tissue, including in live animals. Scattering does, however, severely limit the use of spectral dispersion techniques to improve spectral resolution. In practice, this limited spectral resolution together with the need for multiple excitation wavelengths to excite different fluorophores limits multiphoton microscopy to imaging a few, spectrally distinct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Notably, this is a critical yet straightforward add-on obviating the need for complicated spectral unmixing or post hoc image processing. In contrast, multispectral imaging techniques employ distinct fluorescent biosensors (genetically encoded or chemical-based) [ 22 , 23 ], usually in the same cells. Although very informative, technical challenges (i.e., combining suitable filter settings and establishing complicated spectral unmixing algorithms) undermine implementing these methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this is a critical yet straightforward add-on obviating the need for complicated spectral unmixing or post hoc image processing. In contrast, multispectral imaging techniques employ distinct fluorescent biosensors (genetically encoded or chemical-based) [ 22 , 23 ], usually in the same cells. Although very informative, technical challenges (i.e., combining suitable filter settings and establishing complicated spectral unmixing algorithms) undermine implementing these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one concern about this approach that is still elusive whether a 1:1:1 ratio remains constant over a longer time of passaging, freezing, and thawing cycles. Co-culturing cells with fluorescent reporters is a favored method employed in many studies [ 22 , 23 , 25 ]; however, to our knowledge, such an approach as presented in this study has not been shown elsewhere as a multiparametric imaging technique.…”
Section: Discussionmentioning
confidence: 99%
“…[ 53 ] This technique is particularly attractive in combination with optical multiplexing as it can significantly increase the throughput of (bio)imaging by tracking multiple targets, such as fluorescent proteins or luminescent nanoparticles. [ 54,55 ] The bright field optical microscopy image (Figure 2A2) shows a region containing UCNP‐PGLY beads of similar morphologies. However, when hyperspectral mapping was performed at the regions of interest indicated in green, blue and cyan (magnified in Figure 2B/C1–4 for better visualization), the characteristic spectral profiles of UCNP‐2, UCNP‐3, and UCNP‐4 were unequivocally identified (Figure 2D1–4).…”
Section: Resultsmentioning
confidence: 99%
“…First, TPEF spectra are typically broad (~50 nm), which can make detection of more than 3 fluorophores in vivo difficult. Spectral unmixing has recently been developed to address this challenge, but it still comes at the expense of system complexity and cost due to the use of multiple lasers and computational unmixing 43 . Second, transgenic animals with multiple fluorescent proteins encoding different cell types require extensive breeding, which brings substantial costs in time and resources.…”
Section: Discussionmentioning
confidence: 99%